Ensuring Legal Protection of Biological Diversity Regulations for Safeguarding Ecosystem - Narzullayev, Olim; Anor Mukasheva; Sadikova Dilafruz (Journal of Human Rights, Culture and Legal System, 2025)
The legal protection of biodiversity constitutes a central concern within ecological law theory because it directly contributes to maintaining ecosystem stability and supporting sustainable development. This study aims to analyze the normative framework of biodiversity protection and evaluate its effectiveness in addressing urgent ecological challenges, including species extinction, habitat degradation, and the impacts of climate change. The research employs a normative-legal approach by examining primary and secondary legal materials and applies qualitative analysis to conduct a comparative study of international and national legal standards. The findings demonstrate three critical points. First, although international agreements provide a normative foundation for biodiversity governance, their implementation remains constrained by weak enforcement mechanisms, interpretive ambiguities, limited financial resources, and fragmented institutional coordination. Second, the study highlights the necessity of adopting a holistic and system-based approach to biodiversity governance to confront increasing environmental pressures such as water scarcity, habitat fragmentation, and the decline of endangered species and urban green areas. Third, the research stresses the importance of strengthening institutional capacity and refining legal instruments to secure the long-term resilience of biodiversity initiatives. This study contributes to the development of enforceable and context-sensitive legal strategies, thereby offering valuable insights for policymakers and environmental law practitioners in advancing biodiversity conservation